2020
DOI: 10.1021/acschembio.0c00466
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling of Swainsonine Biosynthesis via a Multibranched Pathway in Fungi

Abstract: The indolizidine alkaloid swainsonine (SW) is a deadly mycotoxin to livestock that can be produced by different plant-associated fungi, including the endophytic entomopathogenic fungi Metarhizium species. The SW biosynthetic gene cluster has been identified but the genetic mechanism of SW biosynthesis remains obscure. To unveil the SW biosynthetic pathway, we performed gene deletions in M. robertsii, heterologous expression of a core biosynthetic gene, substrate feedings, mass spectrometry, and bioassay analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 32 publications
0
41
2
Order By: Relevance
“…Some progress has been made to help understand PA formation during swainsonine biosynthesis. Continuing from the previous identification of the SWN cluster, Luo et al [61] further studied its function in M. robertsii. The disruption of swnA decreased PA by fivefold and therefore it should play an important role in the production of PA.…”
Section: Figurementioning
confidence: 90%
See 3 more Smart Citations
“…Some progress has been made to help understand PA formation during swainsonine biosynthesis. Continuing from the previous identification of the SWN cluster, Luo et al [61] further studied its function in M. robertsii. The disruption of swnA decreased PA by fivefold and therefore it should play an important role in the production of PA.…”
Section: Figurementioning
confidence: 90%
“…In fact, swainsonine producing strains showed slightly less virulence than the knockout mutant. Inoculation experiments showed that by M. robertsii infection did not produce detectable swainsonine in maize (Zea mays), soybean (Glycine max), and milkvetch (Astragalus sinicus) [61]. Thus, the production of swainsonine is not necessary for colonization of those characterized fungi.…”
Section: The Endophyte and The Biosynthesis Of Swainsoninementioning
confidence: 99%
See 2 more Smart Citations
“…For group I and II high‐oxidation state securinega alkaloids, we propose that a direct C4 oxidation would occur in an analogous fashion to the C−H hydroxylation during the swainsonine biosynthesis (Scheme 15). [54,55] Group I high‐oxidation state securinega natural products can undergo further oxidations to group II high‐oxidation state securinega alkaloids. We hypothesize that group III and IV high‐oxidation state securinega alkaloids are all derived from N ‐oxide derivative 163 .…”
Section: Biosynthetic Hypothesismentioning
confidence: 99%